Unraveling team sponsorship in World Cup: What are the influencing factors? - Lee, C.; Bravo, G. (The Sport Journal, 2014)
There are three parties involved in a simple sponsorship mechanism: the sponsor, the sponsored event or team, and the consumers (fans). However, this structure becomes more complicated in some cases where sub-sponsors exist such as in international sporting events. In these cases, would an overarching event influence sub-sponsorship such as team sponsorship? Based on this question, this study aims to investigate the influence of overarching brand on team sponsorship effect, along with consumers` attitudes toward team sponsors, team identification, and patriotism.